Comparative analysis of drought-responsive and -adaptive genes in Chinese wingnut (Pterocarya stenoptera C. DC) - Li, Yong (BMC Genomics, 2021)
BACKGROUND: Drought is the main stress factor for the cultivation of Pterocarya stenoptera in urban areas, and this factor will cause its dehydration and affect its growth. Identifying drought-related genes will be useful for understanding the drought adaptation mechanism of P. stenoptera. RESULTS: We used physiological indicator detection, comparative transcriptome sequencing, and reanalysis on the results of previous landscape genomics studies to investigate the drought adaptation mechanism in P. stenoptera. The changes in malondialdehyde content showed that P. stenoptera was remarkably affected by drought stress, and the increase in soluble sugar content suggested its important role in response to drought stress. Results of comparative transcriptome sequencing showed that P. stenoptera initiated a series of programs, such as increasing the gene expression of unsaturated fatty acids, tyrosine, and plant pathogen resistance, to deal with the transient drought stress. According to the annotated results in a previous study, P. stenoptera adapts to the long-term differential drought stress by regulating the thickness of cell walls and expressing upper or lower limits of the downstream genes in the hormone signaling pathway. Through the comparative analysis of drought-responsive and -adaptive genes in P. stenoptera, this study supports the hypothesis that the environment-responsive genes (ERGs) introduced by the transient environmental stresses will be substantially more than the environment-adaptive genes (EAGs) in response to long-term differential environmental stresses, and the EAGs are not necessarily ERGs. CONCLUSIONS: Our study identified drought-responsive and -adaptive genes in P. stenoptera and revealed that P. stenoptera increased the gene expression of unsaturated fatty acids, tyrosine, and plant pathogen resistance in response to transient drought stress. This study reveals the different adaptation mechanism of P. stenoptera under the transient and long-term differential drought stresses. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12864-021-07470-z.